In vivo CRISPR screening for novel noncoding RNA functional targets in glioblastoma models. Issue 9 (10th May 2021) - Attenello, Frank Joseph; Tsung, Kathleen; Bishara, Isaac; Loh, Yong‐Hwee Eddie; Chen, Thomas C.
Abstract: CRISPR (clustered regularly interspaced short palindromic repeat)‐based genetic screens offer unbiased and powerful tools for systematic and specific evaluation of phenotypes associated with specific target genes. CRISPR screens have been utilized heavily in vitro to identify functional coding and noncoding genes in a large number of cell types, including glioblastoma (GB), though no prior study has described the evaluation of CRISPR screening in GB in vivo . Here, we describe a protocol for targeting and transcriptionally repressing GB‐specific long noncoding RNAs (lncRNAs) by CRISPR interference (CRISPRi) system in vivo, with tumor growth in the mouse cerebral cortex. Given the target‐specific parameters of each individual screen, we list general steps involved in transducing guide RNA libraries into GB tumor lines, maintaining sufficient coverage, as well as cortically injecting and subsequently isolating transduced screen tumor cell populations for analysis. Finally, in order to demonstrate the use of this technique to discern an essential lncRNA, HOTAIR, from a nonessential lncRNA, we injected a 1:1 (HOTAIR:control nonessential lncRNA knockdown) mixture of fluorescently tagged U87 GB cells into the cortex of eight mice, evaluating selective depletion of HOTAIR‐tagged cells at 2 weeks of growth. Fluorescently tagged populations were analyzed via flow cytometry for hiBFP (control knockdown) and green fluorescent protein (HOTAIR knockdown), revealing 17% ( p  = 0.007) decrease in fluorescence associated with HOTAIR knockdown relative to control. The described in vivo CRISPR screening methodology thus appears to be an effective option for identifying noncoding (and coding) genes affecting GB growth within the mouse cortex. Abstract : Lentivirally packaged clustered regularly interspaced short palindromic repeat interference (CRISPRi) library is transduced into glioblastoma cells (1, 000 cells transduced/single guide RNA after drug selection), with transduced cells injected into the mouse cortex, and resected under fluorescence guidance after 2‐week growth. Fluorescence‐activated cell sorting isolates viable, transduced cells, and sequencing of tagged cells identifies specific gene knockdowns associated with in vivo growth.